Community-Based Islamic Education In Urban Society: A Study Of The Shift Pemuda Hijrah Movement - Dilawati, Rika (Fahmina: Jurnal Pendidikan Islam, 2025)
This study explores community-based Islamic education in urban contexts through a qualitative case study of the Shift Pemuda Hijrah movement in Bandung, Indonesia. The research responds to the need for adaptive forms of Islamic education that engage with digital culture while addressing the spiritual and social challenges faced by urban Muslim youth. Using a qualitative descriptive approach, data were collected through semi-structured interviews, participant observation, and document analysis involving primarily active members, mentors, and organisers of the community, whose backgrounds vary in age, social experience, and intensity of participation. The data were analysed thematically to capture the meanings, practices, and pedagogical orientations articulated within the movement. The findings suggest that Shift Pemuda Hijrah functions as a non-formal educational space in which spirituality, social engagement, and ecological awareness are integrated through programmes such as Shift Care, Shift Farm, and Pesan Trend. Learning processes are largely experiential and participatory, combining mentoring, social practice, and digitally mediated da‘wah. These processes are perceived by active participants as fostering reflective spirituality and orientations towards religious moderation (wasatiyyah). However, the study does not claim measurable or long-term behavioural transformation, as the findings are derived from self-reported experiences within a cross-sectional research design.This research also recognises several analytical limitations. The qualitative approach prioritises interpretive depth rather than quantitative assessment of effectiveness or sustainability. Moreover, while the study highlights innovative and positive educational dynamics, it offers limited insight into internal resistance, critical perspectives, or power relations within the community. External factors and interactions with formal religious authorities are acknowledged as influential but remain outside the primary empirical scope of this study. Despite these limitations, the study contributes to scholarship on Islamic education by offering a contextual and critically reflexive understanding of how community-based, digitally mediated learning environments shape contemporary Muslim youth religiosity in urban Indonesia.